2021
DOI: 10.3390/hemato2040041
|View full text |Cite
|
Sign up to set email alerts
|

MRI versus CT and PET/CT in the Preoperative Assessment of Hodgkin and Non-Hodgkin Lymphomas

Abstract: (1) Background: The purpose of this study is to retrospectively compare CT, MRI, and PET/CT in detecting lymphadenopathies and extra-nodal lesions in lymphoma and in disease staging. (2) Methods: Inclusion criteria were the availability of TB (Total Body) CT and/or PET/CT performed before treatment; MRI performed no later than 2 weeks after TBCT; histological confirmation of lymphoma; clinical-diagnostic follow-up. Using these criteria, we included 64/353 patients with TBCT and MRI performed at our hospital; 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In the same study, sensitivity, specificity, and accuracy for the detection of lymph nodes were found to be 96.2%, 97.0%, and 96.7% for MRI and 83.7%, 96.2%, and 90.6% for CT, respectively. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, sensitivity, specificity, and accuracy for the detection of lymph nodes were found to be 96.2%, 97.0%, and 96.7% for MRI and 83.7%, 96.2%, and 90.6% for CT, respectively. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…Disease staging was assessed using the Revised Staging System for Primary Nodal Lymphomas (Supplemental Material - Table 2) [ 4 ]. Nodal involvement was assessed in 10 nodal stations: cervical, supraclavicular, axillary, mediastinal, hilar, para-aortic, mesenteric, iliac, inguinal regions, and other regions (such as liver hilum) [ 26 , 27 ]. Lymph nodes were considered involved when on axial images the largest diameter was greater than 1.5 cm or the short axis was greater than 1 cm or when they coalesced into large nodal masses, the DWI signal was higher than that of the spinal cord, or in the presence of central necrosis, regardless of the diameter [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another gastrointestinal inflammatory disease recently investigated with MRI is the intestinal graft-versus-host-disease (GVHD), a severe acute or chronic complication of hematopoietic stem cell transplantation, difficult to diagnose. Multiparametric MRI can be useful for both diagnosis and staging of acute and chronic GVHD, being able to identify many specific intestinal and extraintestinal signs (biomarkers), such as predominant and continuous small bowel involvement, edema of the intestinal wall, stratified "target" wall appearance on both T2-weighted and post contrast T1-weighted images, subcutaneous fat tissue edema, and mesenteric and retroperitoneal edema [28,29].…”
Section: Multiparametric Mri Evaluation Of Bowel Inflammationmentioning
confidence: 99%